MELIHAT HUBUNGAN MASYARAKAT DALAM PRAKTI - Sri Narti (Professional: Jurnal Komunikasi dan Administrasi Publik, 2016)
Public relations was a management function that planned and sustainable through organizations and private or public institutions to gain understanding, sympathy and support from those who were related or might be related to the study of public opinion among them. PR could keep the credibility of the organization remain good, reached out those who avoid salespeople or advertising; dramatized a company or a specific product as well as the relationship with the mass media. The perspectives of the study was people often perceived public relations as a group of people who twist the facts to turn a bad situation for the benefit of companies. It’s true that part of the public relations goal was to show the positive side of the company that happened. However, public relations ethics required that the works were done in an objective, fair, and transparent ways to the public. Public relation in communication practice was the form of public relations product, which operationally is a form of concrete activities and include efforts to do: employee relations, financial relations, community relations, crisis management communication, relationships public interest / public, consumer education, and relationship development Internet.  Keywords: public relations in practice, product PR, PR event